Responsive teaching in science and mathematics - Robertson, Amy D. 1984-; Scherr, Rachel E.; Hammer, David (Teaching and learning in science series, 2016)
Answering calls in recent reform documents to shape instruction in response to students' ideas while integrating key concepts and scientific and/or mathematical practices, this text presents the concept of responsive teaching, synthesizes existing research, and examines implications for both research and teaching. Case studies across the curriculum from elementary school through adult education illustrate the variety of forms this approach to instruction and learning can take, what is common among them, and how teachers and students experience it. The cases include intellectual products of students' work in responsive classrooms and address assessment methods and issues. Many of the cases are supplemented with online resources (http://www.studentsthinking.org/rtsm) including classroom video and extensive transcripts, providing readers with additional opportunities to immerse themselves in responsive classrooms and to see for themselves what these environments look and feel like.